Biological function of a gC1qR homolog (EcgC1qR) of Exopalaemon carinicauda in defending bacteria challenge. Issue 82 (November 2018) - Zhang, Jiquan; Liu, Yujie; Li, Yanyan; Su, Naike; Zhou, Yaru; Xiang, Jianhai; Sun, Yuying
Abstract: The gC1qR is a ubiquitously expressed cell protein that interacts with the globular heads of C1q (gC1q) and many other ligands. In this study, one gC1qR homolog gene was obtained from Exopalaemon carinicauda and named EcgC1qR . The complete nucleotide sequence of EcgC1qR contained a 774 bp open reading frame (ORF) encoding EcgC1qR precursor of 257 amino acids. The deduced amino acid sequence of EcgC1qR revealed a 55-amino-acid-long mitochondrial targeting sequence at the N-terminal and a mitochondrial acidic matrix protein of 33 kDa (MAM33) domain. The genomic organization of EcgC1qR gene showed that EcgC1qR gene contained five exons and four introns. EcgC1qR could express in all of the detected tissues and its expression was much higher in hepatopancreas and hemocytes. The expression of EcgC1qR in the hepatopancreas of prawns challenged with Vibrio parahaemolyticus and Aeromonas hydrophila changed in a time-dependent manner. The expression of EcgC1qR in prawns challenged with V. parahaemolyticus was up-regulated at 6 h ( p < 0.05), and significantly up-regulated at 12 h and 24 h ( p < 0.01), and then returned to the control levels at 48 h post-challenge ( p > 0.05). At the same time, the expression in Aeromonas -challenged group was significantly up-regulated at 6, 12 and 24 h. The recombinant EcgC1qR could inhibit the growth of two tested bacteria. In addition, we successfully deleted EcgC1qR gene through CRISPR/Cas9 technology and it was the first time to obtain the mutant of gC1qR homolog gene in crustacean. It's a great progress to study the biological function of gC1qR in crustacean in future. Graphical abstract: Highlights: The expression profiles of EcgC1qR was were demonstrated. EcgC1qR was up-regulated after challenge with V. parahaemolyticus or A. hydrophila. EcgC1qR was successfully deleted through CRISPR/Cas9.